DETERMINAN KEMUDAHAN DAN PERSEPSI PENGGUNA TERHADAP IMPLEMENTASI E-PAD PADA PAJAK HOTEL DI KABUPATEN BANYUWANGI DENGAN INTERVENING KEPUASAN WAJIB PAJAK - Wardani, Pramita Sukma (Politeknik Bisnis Indonesia, 2024)
This research aims to determine the effect of convenience on the implementation of E-PAD on hotel taxes by intervening taxpayer satisfaction, the influence of user perceptions on the implementation of E-PAD on hotel taxes in Banyuwangi district with the intervening variable taxpayer satisfaction. This research method uses a quantitative method with data collection techniques using a Google Form questionnaire. The collected data was analyzed with the help of the SmartPLS 4.0 software application. The research results show that the variables of convenience and user perception have a positive effect on the implementation of E-PAD on hoyel taxes by using taxpayer satisfaction interventions.